Implementation Of Ship Crew Health Qualifications Based On The 2006 Maritime Labor Convention (MLC) At PT. Conocophillips At PT. Sejatera Bahari Abadi Palembang Branch - Safrina, Merry; Ulpa, Maria; Syafriyansyah; Peliani , Winda (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to determine the implementation of ship crew health qualifications based on the 2006 Maritime Labor Convention (MLC) at PT. Eternal Maritime Prosperity Palembang. In this research the author used qualitative data. Based on the description and discussion that the author has conveyed in the previous chapter based on data from the field, library and office regarding the Health Qualifications of Ship Crews Based on the 2006 Maritime Labor Convention (MLC) and the PT Health Protocol. Conocophillips at PT. Sejaterah Bahari Abadi Palembang Branch, the author can draw a conclusion from this research, namely that the implementation of crew health qualifications at PT. Sejaterah Bahari Abadi is in accordance with the 2006 Maritime Labor Convention (MLC) regulations.